PERILAKU HARGA DAN KETERPADUAN PASAR CABAI MERAH KERITING (Capsicum annuum) DI PROVINSI BENGKULU - Sandra, Sandra; Asriani, Putri Suci; Rasyid, Witman (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
This research aims to measure of price behavior, market integration and market leader of the red chili in Bengkulu Province. Monthly series of 2006 to 2011 were used as sample data in this analyzing research. The data were from secondary of the monthly average price of red chili. They were obtained from the Central Bureau of Statistics and the Department of Agriculture in Bengkulu Province. The variables which were research included red chili price in the market producer Curup and market consumer Panorama, Minggu, Purwodadi and Ampera. The price behavior applied descriptive statistical analysis, to see the fluctuation of price applied the coefficient of variation formula. The analysis of market integration and marked leader applied the method of co-integration and Granger causality test (Engle and Granger model (1987)). The results of the price behavior showed price of red chili commodity is relative fluctuation. The value of the coefficient of variation (CV) in the consumers area (CV = 42,35%) is smaller than in the producer area (CV = 64,41%). The price of red chili in producer area more fluctuation than the prices in the consumers area. The result of market integration showed a strong level of market integration between market producer Curup and consumer Panorama, Minggu, Purwodadi and Ampera. Besides it, the strong level of integration also between the inter-market consumer Panorama, Minggu, Ampera and Purwodadi. Market leader for commodity red chili in Bengkulu Province is market consumer Panorama.